ChemInform Abstract: Cu(I)‐Catalyzed Tandem Decarboxylative/C—H Activation Coupling of Cyclic Diketones, Proline and Alkynes: Synthesis of α‐Alkynylated Pyrrolidine‐Oxyindoles. Issue 42 (14th October 2014) - Kumar, Atul; Kumar, Mukesh; Gupta, Lalit Prakash; Gupta, Maneesh Kumar
Abstract A variety of pyrrolidinyl oxyindoles are synthesized from one‐pot reaction of isatin derivatives [(I) and (V)], proline (II), and terminal alkynes with aromatic or ester substituents [(III) and (VII)].